International vergleichende Sportwissenschaft - Ziemainz, H.; Roger, U. (Leipziger Sportwissenschaftliche Beiträge, 2005)
Sport which presents an international phenomena per se, and with it also sport sport science (see Haag & Schroder, 2005), are to a great extend confronted with actual tendencies of golbalisation and internationalisation. In this paper, actual approaches of international comparative sports science will be presented, especially a theory guided qualitative and quantitative approach. Furthermore, possiblities and consequences of international comparative sport science will be discussed.